A Comparative Study of the Teachings of Panca Sradha in Hinduism and the Concept of Faith in Islam - Juita Juita; Indra Harahap (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to provide a comparative analysis of the belief system of Panca Sraddha in Hinduism and the pillars of faith (rukn al-iman) in Islam through a text-based comparative theological approach. The research is motivated by the growing need to understand the theological foundations of two major religions that are often simplistically juxtaposed in interfaith discourse. Employing library research as its method, this study applies philosophical hermeneutics and reflective engagement with sacred texts, including the Bhagavad Gita, Upanishads, Vedas, and the Qur’an. The findings reveal that while Panca sraddha and the Islamic pillars of faith serve similar normative functions as the foundations of belief, they differ significantly in terms of epistemological, ontological, and soteriological structures. These differences are particularly evident in concepts such as Brahman–Allah, atman–ruh, karma–deeds, punarbhava–punarbhava-the Day of Judgment, and moksa–heaven. The study contributes to the development of interreligious discourse in Indonesia by offering a theologically grounded and context-sensitive analytical framework. Nonetheless, the research has limitations, including restricted access to traditional Hindu commentaries and limited direct engagement with religious authorities from both traditions. These challenges underscore the need for further studies employing interdisciplinary and collaborative approaches to deepen interreligious understanding.